Characterization of the Antibody and Interferon-Gamma Release Response after a Second COVID-19 Booster Vaccination - Katharina Grikscheit; Holger F. Rabenau; Zahra Ghodratian; Marek Widera; Alexander Wilhelm; Tuna Toptan Grabmair; Sebastian Hoehl; Emily Layer; Fabian Helfritz; Sandra Ciesek (Vaccines, 2022)
The emergence of SARS-CoV-2 Omicron subvariants prompted countries to call for accelerated booster vaccinations to limit disease and transmission. Here, we characterized correlates of protection over time after the second booster or after Omicron BA.1 infection comparing variants of concern (VOCs). Sera from subjects before and two and seven weeks after the second booster or after Omicron infection were examined for the level of Spike receptor-binding-domain (RBD)-specific antibodies. Furthermore, neutralizing antibodies (nABs) were characterized in in vitro neutralization assays comparing the variants of concern Alpha, Beta, Delta, and Omicron BA.1 and BA.2 against the ancestral strain B.1. Here, the second booster resulted in an increase in anti-RBD-IgG-antibodies, remaining nearly constant over time, accompanied by an increase in nABs against B.1 and the VOCs Alpha, Beta, Delta, and Omicron BA.1 and BA.2. However, compared to B.1, the neutralizing capacity against the Omicron subvariants remained low and was limited after the second booster vaccination. This indicates that antibody-mediated protection against infection with this VOC is unlikely, as evidenced by the fact that three individuals of our study cohort became infected with Omicron BA.1 after the second booster. T cell activation was measured by interferon-gamma release assays in a subgroup of subjects and was increased in all subjects tested after the second booster vaccination, correlating with the amount of Spike-specific antibodies. In subjects with Omicron BA.1 breakthrough infection, a significant increase in nABs to all VOCs studied was observed independently of booster vaccinations. Taken together, our data indicate that a second booster or Omicron BA.1 infection mediate a substantial increase in anti-Spike IgG antibodies; however, infection with Omicron BA.1 induced a stronger increase in neutralizing antibodies against the different VOCs